IMPROVING THE EFFICIENCY OF HIGH-SPEED MILLING OF THIN-WALLED ELEMENTS OF PARTS OF COMPLEX GEOMETRIC SHAPES - Anton Germashev; Victor Logominov; Yelena Kozlova; Vladimir Krishtal (Сучасний стан наукових досліджень та технологій в промисловості, 2017)
Thin-walled elements of complex geometric shapes are widely used in the aerospace and other industries. They are obtained by various methods of machining using modern numerically controlled machines. The fundamental factors for manufacturing of parts are the productivity and machining quality. The subject matter of the article is the vibration during high-speed milling of thin-walled elements of parts of complex geometric shapes. The aim of the article is to determine the possibility of increasing the efficiency of high-speed milling of thin-walled parts by finding vibration-proof processing conditions. To achieve the goal, the following tasks have been set and implemented: considering the features of high-speed milling of thin-walled elements of parts with complex geometric shapes, developing a technique for investigating the milling process, and identifying stable machining conditions for high-speed milling of thin-walled components. The methods of oscillation fixation during machining and statistical analysis of experimentally obtained results are used. The following results are obtained: the design of the experimental bench is suggested to study the process of milling thin-walled elements of parts, the technique of obtaining a quantitative characteristic of the milling conditions, which is based on determining the position of a part at the moment when a milling tooth is cutting into it is offered, and the stable machining conditions for high-speed milling of thin-walled elements of parts are determined. Conclusions. The decisive role of the spindle rotational velocity in achieving a low vibration level has been experimentally proven, under the conditions of high-speed milling in a vibration-resistant range of spindle velocities both the radial depth and the feed can be increased without losses in the quality of machining.